THE ROLES OF SOCIAL MEDIA ONLINE AND COMMUNITY TO CUSTOMER DECISIONS - Dimas Satriawan Sriparno (Universitas Pendidikan Nasional, 2013)
purpose of this study were 1) to determine and analyze the effect of theinteraction between departments on the performance of services, 2) to identify and analyzethe effect on the performance of the marketing information system services, 3) To identify andanalyze the influence of environmental observations on the performance of the service. And4) to identify and analyze the effect of service performance against business achievements.Respondents of this study were employees of Bank BNI 46 Main Branch Office Renon,amounting to 101 people. Collecting data in this study using a questionnaire containing 15questions, each question using 10 alternative answers. Analysis of the data used to answerthe research questions and test hypotheses influence the interactions between multipledepartments, marketing information systems, environmental monitoring, business serviceperformance and achievement of statistical methods used Structural Equation Modeling(SEM) with AMOS software version 20The results showed that: 1) This research proves that the interaction betweendepartments in a positive effect on the performance of the service so that it can be said thatthe higher the interaction between departments of a company, then the performance of theservices the company will get better. 2) marketing information systems positively affect theperformance of the service, so it can be said that the better the marketing information systemthat is used, the quality of service provided will be the better. 3) Observation of a positiveenvironmental effect on the performance of the service, so it can be said that the bettercompanies in observing the environment, the better the quality of the company's services and4) the performance of services positively affect the achievement of the company's business, soit can be said that the higher the firm in providing better service the better the achievement ofthe company's businessKeywords : online social media, community, brand awareness, attitude toward brand, customer decision